1、 d 2 2 u d l h f = du = Re R e d d e d e 4 = A d e 4 =4 = + moody Re C = Re 64 = C (P41 1-3) = + inertia contract vena A-A 90 45 2 2 u h f = 2 2 u p f = g u H f 2 2 = u P43 1-2 1 2 2 2 1 1 = A A 1 , 0 2 1 = e A A exit 1 2 2 1 2 1 5 . 0 = A A 5 . 0 , 0 1 2 = c A A come into 2 1 5 . 0 = A A A 2 1 5 .
2、0 = A A 2 2 u d l h e f = l e m d m u 1-20 2 2 u d l p e f = g u d l H e f 2 2 = l e P43 1-26 P43 1-2 l e /d 2 2 2 2 2 2 3 2 2 u u u e + = 2 2 2 2 2 2 2 2 2 2 1 1 1 u d l u p gz u p gz + + + = + + 2 2 2 2 2 2 2 2 3 3 3 2 1 1 1 2 u u d l u p gz u p gz e + + + + = + + 1 2 3 p 3 u 3 =0 e =1 2 2 2 2 2 2
3、 u u e u3 0 A3 A2 u3u2 0 0 P66 1-24 P57 P134 3 P64 1-31 0 h 2 1 ( ) + + = + = 2 2 2 2 2 2 u u d l u d l h h h e f f f 2 ) ( 2 u d l l e + + = J/kg 2 2 u d l l h h h e c i e i f f f + + + + = + = 1 0.5 2 2 u d l l p p p e f f f + + = + = J/m 3 Pa g u d l l H H H e f f f 2 2 + + = + = J/N m 1 2 V s A
4、V u s = 2 4 d A = u V d s 4 = V s u d 2 2 u d l h f = u d l u d l 2 2 32 2 (Re) = 2 ) (Re, 2 u d l d ) ( f = 2 ) ( 2 u d l d 2 u u u h f w e 2 1 = x u x + + + = f e h p u z W ) 2 ( 2 m 3 /s N e = V s .W e u opt u V s u d u d P357 P381 p17 1-1 p50 1-3 p26 1-1 p50 1-3 P314 P381 1 t cons V V V n s s s
5、tan , 2 , 1 , = = = L + + = n f f f f h h h h , 2 , 1 , L2 moody u d V s 4 2 = + + + = + + f h p u gz p u gz 2 2 2 2 1 2 1 1 2 2 2 ) ( 2 u d l h f + = ) , ( d du f = 3 n n-3 3 3 3 3 f s h V d l , , , 1-20 h 2 1 f h u p gz u p gz + + + = + + 2 2 2 2 2 2 2 1 1 1 0 gh z z g h f = = ) ( 1 2 1-18 2 ) ( 2
6、 u d l h i i f + = g u d l h i i 2 ) ( 2 + = 4 / 2 d V u s = = 27 1 / Re d du moody 1 2 s f V u d l h , , , 1-21 2 2 u d l h f = l h d u f = 2 u Re 1 2 (1) ) , ( d du f = (2) moody = u = 2 2 001 . 0 27 1 / Re 1 2 1 = + i i d du u L moody u 1 27 1 / Re = d du u 2 * moody 2 * u p26 1-1 p50 1-3 1 1-21
7、1-23 2 3 4 8 d l V h s f , , , 1-20 4 2 d V u s = f h lu d = 2 2 2 2 u d l h f = 5 2 2 8 = f s h lV d Re 1 2 ) , ( d du f = moody 2 2 001 . 0 27 1 / Re 1 2 1 = + i i d du d L = d = moody 3 3 2 2 1 1 2 3 E E h f = 1 3 E E h f = = 2 2 1 f h E E + = 2 1 1 2 1 E E h f = 0 3 3 2 2 1 1 1 2 E E 3 2 E E h f = 3 1 E E h f = 28 2 p gz u E + + = 2 2 A A B B A E A E A E A E B E B E B E B E 1 A A B B A E A E A E A E B E B E B E B E A A A A A E E E E B B B B E E E E